Dietary Fat and Fiber Intakes Are Not Associated with Patterns of Urinary Estrogen Metabolites in Premenopausal Women. Issue 9 (15th July 2015) - Oh, Hannah; Smith-Warner, Stephanie A; Tamimi, Rulla M; Wang, Molin; Xu, Xia; Hankinson, Susan E; Fuhrman, Barbara J; Ziegler, Regina G; Eliassen, A Heather
Abstract: Background: Interindividual differences in the bioavailability of potentially carcinogenic estrogen and estrogen metabolites (EMs) may play a role in the risk of breast cancer. Objective: We examined whether dietary intakes of fiber and fat influence premenopausal EM profiles through effects on estrogen synthesis, metabolism, or excretion. Methods: We conducted a cross-sectional analysis of 598 premenopausal women who participated in a reproducibility study ( n = 109) or served as controls in a nested case-control study of breast cancer ( n = 489) within the Nurses' Health Study II. Dietary intakes of fiber and fat were assessed via semiquantitative food frequency questionnaires in 1995 and 1999. Midluteal urine samples were collected between 1996 and 1999 and EMs were quantified with the use of HPLC-tandem mass spectrometry. Linear mixed models were used to estimate creatinine-adjusted geometric means for individual EMs and their pathway groups across categories of dietary intake while controlling for total energy intake and potential confounders. Results: Higher total dietary fiber intake (>25 g/d vs. ≤15 g/d) was associated with significantly higher concentrations of 4-methoxyestradiol (50% difference, P -difference = 0.01, P -trend = 0.004) and lower concentrations of 17-epiestriol (−27% difference, P -difference = 0.03, P -trend = 0.03), but was not associated with any other EMs. The associations did not vary by fiber intake from different sources. Total fat intake (>35% energy vs. ≤25% energy) was suggestively positively associated with 17-epiestriol (22.6% difference, P -difference = 0.14, P -trend = 0.06); the association was significant for polyunsaturated fatty acid (37% difference, P -difference = 0.01, P -trend = 0.01) and trans fat (36.1% difference, P -difference = 0.01, P -trend = 0.01) intakes. Conclusion: Fiber and fat intakes were not strongly associated with patterns of estrogen metabolism in premenopausal women. Our data suggest estrogen metabolism is not a major mechanism through which dietary fiber and fat may affect breast or other hormone-related cancer risks.